Self-Initiated Intervention pada Pasien Diabetes Melitus Tipe II dengan Keluhan Nyeri Neuropati Perifer - Firstayude, Niswatul Imtinan; Yulia, Yulia (Journal of Telenursing (JOTING), 2024)
This literature aims to explore the effectiveness of various self-initiated interventions in managing neuropathic pain among individuals with type 2 diabetes mellitus. The research method involved a systematic review of literature from PubMed, ScienceDirect, and Scopus databases, covering the past five years (2019-2024). The results indicated that ten articles discussed self-initiated interventions, including warm salt baths, cognitive-behavioral therapy, acceptance and commitment therapy, physical exercise, aromatherapy, progressive muscle relaxation, and mindfulness. In conclusion, this literature review highlights the significance of self-initiated interventions in managing neuropathic pain among individuals with type 2 diabetes mellitus, thereby improving their quality of life. Keyword : Neuropathy Diabetic, Non-Pharmacological, Pain, Self-initiated.